Russian version of BRIEF2 Teacher Forms: validation study in typically developing children aged 5 to 7 years old - Gavrilova, Margarita; Aslanova, Margarita; Tarasova, Kristina; Zinchenko, Yuri (Frontiers in Psychology, 2023)
This study examined the psychometric properties of the Russian version of the Behaviour Rating Inventory of Executive Function (BRIEF2) Teacher Form. The study sample consisted of 178 typically developing children aged 5 to 7 years. Two preschool teachers (for children aged 5 and 6 years) and one school teacher (for children aged 7 years) completed the Russian BRIEF2 questionnaire. The results showed that the Russian version of the BRIEF2 had good internal reliability for the composite indices and Global Executive Composite, and good or acceptable internal consistency of subscales except for the Initiate subscale. Interrater reliability between the individual children ratings evaluated by two preschool teachers was adequate except for the Plan subscale for five-year-old and the Initiate subscale for six-year-olds. Regarding construct validity, CFA showed that the three-factor solution was the best model, confirming the reliability of the interpretation of the three indices (behaviour, emotion and cognitive) for the Russian version of the BRIEF2.